Life History of Erotylina jaspidea (Erichson, 1847) (Coleoptera, Erotyloidea, Erotylidae, Erotylini) - Xavier, Miguel Dorcino; Pecci-Maddalena, Italo Salvatore De Castro; Lopes-Andrade, Cristiano; Baseia, Iuri Goulart (Zootaxa, 2022)
The life history of Erotylina jaspidea (Erichson, 1847) (Coleoptera, Erotyloidea, Erotylidae, Erotylini) is described. A female specimen was found in an Atlantic Forest remnant in Northeast Brazil. After oviposition, individuals were reared in Petri dish and terrarium, feeding on basidiomes of Lentinus substrictus (Bolton) Zmitr. & Kovalenko, Favolus tenuiculus P. Beauv (Polyporaceae) and an unidentified resupinate fungus. Growth and feeding behaviors were regularly observed. We provide information on the observed life history stages, together with morphological descriptions, and photographs of eggs, larvae, pupae and adults. We compared our description of the teneral E. jaspidea to species of similar color pattern. Furthermore, we discuss hypotheses about larval defensive behavior and total instar durations in E. jaspidea and other Erotylinae representatives. The present work is the first to provide a description for the life history of a species of the genus Erotylina.